Graphite negative electrode material and preparation method and application thereof
By doping nitrogen and phosphorus elements into the graphite negative electrode material, the problem of high lithium ion diffusion resistance is solved, the material's conductivity and stability are improved, and the fast charging and cycling performance of lithium batteries is improved.
Patent Information
- Application Number
- CN202411606175.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high diffusion resistance of lithium ions in the graphite structure leads to poor rate and capacity performance of lithium batteries. Although nitrogen doping can improve conductivity, it affects the structural stability of graphite.
The graphite negative electrode material is prepared by acid oxidation treatment and pyrolysis methods, and the doping amount of nitrogen and phosphorus elements is controlled to improve conductivity and stability.
Improve the embedded/migration capacity of lithium ions, improve the fast charging performance and rate performance of the material, optimize the transmission path of lithium ions, extend the battery cycle life, and form a more stable and uniform solid electrolyte interface, reducing irreversibility Capacity loss.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of new energy materials, and specifically relates to a graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Graphite is widely used as the main active negative electrode material in lithium batteries due to its excellent properties, such as low working potential, high conductivity, good life, high efficiency, etc. However, the anisotropic structure of graphite limits the free diffusion of lithium ions in the graphite structure, which leads to high lithium ion diffusion resistance and poor rate performance and capacity performance.
[0003] In response to these problems, experts and scholars in the field have carried out corresponding research in the hope of improving its electrochemical performance. At present, one of the most studied methods is to dope natural graphite with nitrogen. Nitrogen doping can introduce additional electrons and improve the conductivity of graphite. However, nitrogen doping will introduce defects in graphite and affect the structural stability of graphite. Summary of the invention Therefore, the technical problem to be solved by the present application is to overcome the defects in the prior art such as high diffusion resistance of lithium ions in graphite structure, and that although nitrogen doping treatment can improve the conductivity of graphite materials, it will affect the stability of graphite materials, thereby providing a graphite negative electrode material and its preparation method and application.
[0004] To this end, this application provides the following technical solutions: According to one aspect of the present application, a graphite negative electrode material is provided, including acid-oxidized graphite, wherein the acid-oxidized graphite is doped with nitrogen and phosphorus, and based on the total mass of the graphite negative electrode material, the doping amount of the nitrogen element is 0.5-3%, and the doping amount of the phosphorus element is 0.5-4%.
[0005] As an example, based on the total mass of the graphite negative electrode material, the doping amount of the nitrogen element is 0.5%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 3%, or any range thereof; the doping amount of the phosphorus element is 0.5%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, or any range thereof.
[0006] In some optional embodiments, the specific surface area of the graphite negative electrode material is 1-3m 2 g -1 As an example, the specific surface area of the graphite negative electrode material is 1m 2 g -1 , 1.5m 2 g -1 , 2m 2 g-1 , 2.5m 2 g -1 , 3m 2 g -1 , or within a range consisting of any of the above values.
[0007] In some optional embodiments, under a pressure of 10 MPa, the powder resistivity of the graphite negative electrode material is 0.5-2Ω·m; as an example, the powder resistivity of the graphite negative electrode material is 0.5Ω·m, 0.8Ω·m, 1Ω·m, 1.2Ω·m, 1.5Ω·m, 1.7Ω·m, 2Ω·m, or within a range composed of any of the above values.
[0008] In some optional embodiments, the OI value of the graphite negative electrode material is 1-10; as an example, the OI value of the graphite negative electrode material is 1, 2, 3, 5, 7, 8, 9, 10, or within a range consisting of any of the above values.
[0009] And / or, the degree of graphitization of the acid-oxidized graphite is 90-98%; as an example, the degree of graphitization of the acid-oxidized graphite is 90%, 92%, 94%, 96%, 98%, or within a range consisting of any of the above values.
[0010] According to another aspect of the present application, a method for preparing the above-mentioned graphite negative electrode material is provided, comprising the following steps: S1, using an acid solution containing nitric acid to perform acid oxidation treatment on graphite to obtain acid oxidized graphite; S2, mixing the acid-oxidized graphite with a nitrogen source and a phosphorus source, and pyrolyzing them at 600-1200° C. for 0.5-2 h to obtain the graphite negative electrode material.
[0011] As an example, the pyrolysis temperature is 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or within the range of any of the above values; the pyrolysis time can be 0.5h, 1h, 1.5h, 2h, or within the range of any of the above values.
[0012] In some optional embodiments, in step S2, the mass ratio of the acid-oxidized graphite, the nitrogen source, and the phosphorus source is 1:5-30:5-20. As an example, the mass ratio of the acid-oxidized graphite, the nitrogen source, and the phosphorus source is 1:5:5, 1:30:20, 1:10:15, 1:20:8, 1:25:12, or within the range of any of the above values.
[0013] In some optional embodiments, in step S2, the nitrogen source includes at least one of urea, biuret, melamine, amino acid or ammonium carbonate; And / or, the phosphorus source includes at least one of sodium tripolyphosphate, red phosphorus, phosphoric acid, triphenylphosphine, and phosphorus pentachloride.
[0014] In some optional embodiments, in step S1, the nitric acid-containing acid solution comprises concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:4-4:1; as an example, the volume ratio of concentrated sulfuric acid and concentrated nitric acid is 1:4, 1:3, 3:1, 4:1, 2:2, 2.5:1.5, 1.2:2.4, or within a range composed of any of the above values.
[0015] The concentration of the concentrated nitric acid is 55%-70%; the concentration of the concentrated sulfuric acid is 95%-98%.
[0016] In some optional embodiments, in step S1, the acid oxidation treatment time is 12-36 hours; And / or, the temperature of the acid oxidation treatment is 15-20°C; as an example, the acid oxidation treatment can be placed in an ice water bath to control the reaction temperature within the range of 15-20°C. As an example, the time of the acid oxidation treatment is 12h, 18h, 20h, 24h, 28h, 32h, 36h, or within the range of any of the above values; the temperature of the acid oxidation treatment is 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, or within the range of any of the above values.
[0017] And / or, the usage ratio of the graphite to the acid solution containing nitric acid is 1g:1-20mL; as an example, the usage ratio of the graphite to the acid solution containing nitric acid is 1g:1mL, 1g:5mL, 1g:8mL, 1g:10mL, 1g:15mL, 1g:20mL, or within the range of any of the above values.
[0018] According to another aspect of the present application, a secondary battery is provided, comprising the above-mentioned graphite negative electrode material or the graphite negative electrode material prepared by the above-mentioned preparation method.
[0019] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0020] In the present application, the graphite may be at least one of artificial graphite and natural graphite.
[0021] Specifically, the method for preparing the graphite negative electrode material in the present application may include the following steps: (1) Mix artificial graphite powder and acid solution containing nitric acid, stir in an ice bath for 12-36 hours, and then wash with deionized water several times to remove all acid residues until the solution reaches a neutral pH. Then dry in a vacuum drying oven at 70-100°C for 12-36 hours to obtain acid-oxidized graphite; (2) The obtained acid-oxidized graphite is mixed with a certain amount of nitrogen source and phosphorus source, ball-milled for 1 min-1 h, and then placed in a protective gas for high-temperature pyrolysis, and naturally cooled to obtain the graphite negative electrode material.
[0022] In some optional embodiments, the raw material of artificial graphite is selected from any one of petroleum coke, needle coke, and asphalt coke, or a combination of at least two thereof; the Dv50 of the artificial graphite is 8-18 μm, and the OI value is 3-12.
[0023] In some optional embodiments, the ball milling adopts a dry milling or wet milling operation mode.
[0024] In some optional embodiments, the protective gas is at least one of nitrogen, argon, and ammonia.
[0025] In some optional embodiments, the present application provides a secondary battery, wherein the graphite negative electrode material is used as a negative electrode active material, dissolved in a solvent with a conductive agent and a binder to form a negative electrode slurry, which is coated on a current collector to obtain a negative electrode sheet, and the mass ratio of the negative electrode active material, the conductive agent and the binder is 92-98:0.5-2:1.5-7.5; Optionally, the conductive agent is at least one of carbon fiber, conductive carbon black, carbon nanotube or graphene; Optionally, the binder is one or more of polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose, and styrene-butadiene rubber.
[0026] In some optional embodiments, the compaction density of the negative electrode sheet is 1.40-1.70 g / cm 3 The double-sided coating density of the negative electrode sheet is 100-300 mg / cm 2 The thickness of the negative electrode sheet after rolling is 80-150μm.
[0027] The secondary battery provided in the present application also includes a positive electrode sheet, a separator and an electrolyte. In addition to using the above-mentioned graphite negative electrode material as the negative electrode active material, other components and preparation methods are conventional in the field and are not specifically limited here.
[0028] In the electric device provided in the present application, the secondary battery can be used as a power source of the electric device, or as an energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0029] The technical solution of this application has the following advantages: The graphite negative electrode material provided in the present application includes acid-oxidized graphite, wherein the acid-oxidized graphite is doped with nitrogen and phosphorus, and the doping amount of the nitrogen element is 0.5-3%, and the doping amount of the phosphorus element is 0.5-4% based on the total mass of the graphite negative electrode material. Among them, the acid-oxidized graphite is a thin expanded graphite layer, which expands the interlayer space compared to conventional block graphite materials, is conducive to the insertion / migration of lithium ions, thereby improving the fast charging performance of the material, and also creates more favorable conditions for subsequent element doping; the co-doping of nitrogen and phosphorus not only improves the electronic conductivity and reduces the powder resistivity of the graphite negative electrode material, but also optimizes the transmission path of lithium ions and improves the rate performance. At the same time, co-doping helps to form a more stable and uniform solid electrolyte interface (SEI) film and reduce irreversible capacity loss. Compared with single doping (doping only nitrogen or phosphorus), N / P co-doping has significant advantages and can effectively make up for the shortcomings of single element doping. Specifically, nitrogen doping usually introduces defects in the graphite structure, which will affect the structural stability of the graphite material, and the presence of defects is conducive to the doping of phosphorus (since phosphorus has a large atomic radius, it is difficult to achieve effective doping of phosphorus if the graphite material is directly doped with phosphorus). At the same time, phosphorus can improve the stability of the overall structure of the material by filling some defects or enhancing the interlayer bonding force. The large atomic radius of phosphorus can alleviate the expansion of the graphite layer during the lithium ion embedding process to a certain extent, extending the battery cycle life. Nitrogen doping can introduce additional electrons to improve the conductivity of graphite, while phosphorus doping can also form new electronic states with the graphite structure through its lone electron pairs, further improving the conductivity. Co-doping of nitrogen and phosphorus can form more active sites on the surface and edge of graphite, increasing the storage capacity of lithium ions. If the nitrogen / phosphorus content is too high, it is easy to introduce too many structural defects, causing the material to easily delaminate or break during the cycle, affecting the cycle stability; if it is too little, the improvement effect is not obvious, the element distribution is also prone to unevenness, and the material is unstable.
[0030] The graphite negative electrode material provided in the present application can balance the influence of the specific surface area on the active sites of the material and the side reactions with the electrolyte by limiting the specific surface area.
[0031] The graphite negative electrode material provided in the present application can further improve the fast charging performance of the graphite negative electrode material by limiting the OI value. Generally speaking, the smaller the OI value, the better the fast charging performance. The OI value can characterize the consistency of the grain orientation in the graphite material. The smaller the OI value, the better the isotropy of the material, which is more conducive to Li + The diffusion inside the negative electrode material, so the high rate charging performance is better; however, if the OI value is too low, the highly isotropic graphite structure may lack sufficient crystal orientation support, resulting in a decrease in the mechanical strength and toughness of the material and an inability to effectively disperse stress, leading to local stress concentration and causing structural instability or cracking.
[0032] The preparation method of graphite negative electrode material provided in the present application firstly performs acid oxidation treatment on the graphite material to convert the graphite layer into a thin expanded graphite layer, which can expand the interlayer space; the defects (such as vacancies, edge defects and multi-ring structures, etc.) and oxygen functional groups introduced on the graphite surface by acid treatment can provide more physical and chemical embedding positions for the doping elements, which can effectively stabilize the doping elements and prevent them from migrating or agglomerating during subsequent treatment; then, the mixed pyrolysis with nitrogen source and phosphorus source is carried out under specific conditions to achieve effective doping of N / P elements. The method is simple in process, easy to control, and convenient for popularization and application.
[0033] The preparation method of the graphite negative electrode material provided in the present application can make the distribution of nitrogen and phosphorus in the graphite negative electrode material more uniform by limiting the nitrogen source and phosphorus source, thereby further improving the various properties of the material.
[0034] The preparation method of the graphite negative electrode material provided in the present application can not only slow down the reaction rate and control the orderly progress of the reaction by limiting the acid oxidation treatment temperature, but also improve the selectivity of the product and avoid the excessive generation of by-products. At the same time, it also avoids the risk of excessively violent high-temperature reactions, which may cause accidents or explosions. DETAILED DESCRIPTION
[0035] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0037] Example 1 This embodiment provides a graphite negative electrode material, and its preparation method and specific operating parameters are as follows: (1) Take 5 g of artificial graphite powder (Dv50 = 15.4 μm, OI value = 4.2) and mix it with 60 mL of acid solution (96% concentrated sulfuric acid: 60% concentrated nitric acid, volume ratio 2:1), stir it in an ice bath for 24 hours, control the system temperature between 15-20 °C, and then wash and vacuum dry it at 80 °C for 24 hours to obtain acid-oxidized graphite powder.
[0038] (2) The obtained acid-oxidized graphite powder was mixed with a certain amount of urea and red phosphorus (mass ratio of graphite powder: urea: red phosphorus = 1:15:10) and ball-milled for 1 h, then placed in argon gas at 950°C for 1 h for high temperature pyrolysis, and naturally cooled to obtain a graphite negative electrode material.
[0039] Example 2 This embodiment provides a graphite negative electrode material, and its preparation method and specific operating parameters are as follows: (1) Take 5 g of artificial graphite powder (Dv50 = 8.6 μm, OI value = 2.95) and mix with 5 mL of acid solution (96% concentrated sulfuric acid: 60% concentrated nitric acid, volume ratio 2:1), stir in an ice bath for 12 hours, control the system temperature between 15-20 °C, and then wash and vacuum dry at 80 °C for 24 hours to obtain acid-oxidized graphite powder.
[0040] (2) The obtained acid-oxidized graphite powder was mixed with a certain amount of urea and red phosphorus (the mass ratio of graphite powder: urea: red phosphorus = 1:5:5) and ball-milled for 1 h, then placed in argon gas at 600°C for 0.5 h for pyrolysis, and naturally cooled to obtain a graphite negative electrode material.
[0041] Example 3 This embodiment provides a graphite negative electrode material, and its preparation method and specific operating parameters are as follows: (1) 5 g of artificial graphite powder (Dv50 = 16.8 μm, OI value = 8.3) was mixed with 100 mL of acid solution (96% concentrated sulfuric acid: 60% concentrated nitric acid, volume ratio 2:1), stirred in an ice bath for 36 hours, the system temperature was controlled between 15-20 °C, and then washed and vacuum dried at 80 °C for 24 hours to obtain acid-oxidized graphite powder.
[0042] (2) The obtained acid-oxidized graphite powder was mixed with a certain amount of urea and red phosphorus (mass ratio of graphite powder: urea: red phosphorus = 1:30:20) and ball-milled for 1 h, then placed in argon gas at 1200°C for 2 h for high temperature pyrolysis, and naturally cooled to obtain a graphite negative electrode material.
[0043] Example 4 This embodiment provides a graphite negative electrode material. Compared with Embodiment 1, the only difference is that an equal mass of biuret is used instead of urea in step (2).
[0044] Example 5 This embodiment provides a graphite negative electrode material. Compared with Embodiment 1, the only difference is that an equal mass of melamine is used instead of urea in step (2).
[0045] Example 6 This embodiment provides a graphite negative electrode material. Compared with Embodiment 1, the only difference is that an equal mass of triphenylphosphine is used instead of red phosphorus in step (2).
[0046] Example 7 This embodiment provides a graphite negative electrode material. Compared with Embodiment 1, the only difference is that an equal mass of sodium tripolyphosphate is used instead of red phosphorus in step (2).
[0047] Comparative Example 1 This comparative example provides a graphite negative electrode material, which is different from Example 2 only in that an equal mass of urea is used instead of red phosphorus in step (2).
[0048] Comparative Example 2 This comparative example provides a graphite negative electrode material, which is different from Example 2 only in that an equal mass of red phosphorus is used instead of urea in step (2).
[0049] Comparative Example 3 This comparative example provides a graphite negative electrode material. Compared with Example 2, the only difference is that the artificial graphite is not subjected to acid oxidation treatment, that is, step (2) is directly performed without step (1).
[0050] Comparative Example 4 This comparative example provides a graphite negative electrode material, and its preparation method and specific operating parameters are as follows: (1) Take 5 g of artificial graphite powder (Dv50 = 15.4 μm, OI value = 4.2) and mix it with 60 mL of acid solution (96% concentrated sulfuric acid: 60% concentrated nitric acid = 2:1), stir it in an ice bath for 24 hours, control the system temperature between 15-20°C, and then wash and vacuum dry it at 80°C for 24 hours to obtain acid-oxidized graphite powder.
[0051] (2) The obtained acid-oxidized graphite powder was mixed with a certain amount of urea and red phosphorus (mass ratio of graphite powder: urea: red phosphorus = 1:4:30) and ball-milled for 1 h, then placed in argon gas at 950°C for 1 h for high temperature pyrolysis, and naturally cooled to obtain a graphite negative electrode material.
[0052] Comparative Example 5 (1) Take 5g of artificial graphite powder (Dv50 = 15.4μm, S BET =1.12m 2 g -1 , OI value = 4.2) and 60mL of acid solution (96% concentrated sulfuric acid: 60% concentrated nitric acid = 2:1), stirred in an ice bath for 24 hours, the system temperature was controlled between 15-20°C, and then washed and vacuum dried at 80°C for 24 hours to obtain acid-oxidized graphite powder.
[0053] (2) The obtained acid-oxidized graphite powder was mixed with a certain amount of urea and red phosphorus (mass ratio of graphite powder: urea: red phosphorus = 1:40:4) and ball-milled for 1 h, then placed in argon gas at 950°C for 1 h for high temperature pyrolysis, and naturally cooled to obtain a graphite negative electrode material.
[0054] Test Case 1. N and P element content It can be obtained by X-ray photoelectron spectroscopy (XPS).
[0055] 2. Specific surface area Obtained by Brunauer-Emmett-Teller (BET) method.
[0056] 3. Powder resistivity Measured by four-probe method.
[0057] 4. Graphitization degree Measured by X-ray diffraction (XRD) method.
[0058] 5. OI value Measured by X-ray diffraction (XRD) method.
[0059] 6. Specific capacity Button assembly: Negative electrode sheet preparation: At 25°C, the graphite negative electrode material, conductive carbon black, CMC and SBR prepared in each embodiment and comparative example were mixed in water at a mass ratio of 95.5:1.5:1.5:1.5 to prepare a slurry; the slurry was evenly coated on the opposite sides of the 6um copper foil, and then the copper foil was placed in a vacuum drying oven at 95°C for 2.5 hours. The dried electrode sheet was cut into a disc with a diameter of 16mm, and the coating weight was 20mg (excluding the copper foil). Assembly of half-cell: The prepared electrode was transferred into an inert atmosphere glove box, and the metal lithium sheet was used as the counter electrode. The above-obtained disc was used as the working electrode, and a polyethylene diaphragm with a diameter of 26 mm was used as the battery diaphragm. A low-temperature electrolyte LiPF6 with a concentration of 1 mol / L (the solvent was DMC / EC / EMC / VC with a volume ratio of 1:1:1:1) was added to prepare a CR2430 button cell. The compacted density of the negative electrode material was 1.60 g / cm 3 The assembled battery was left to stand at room temperature for 16 hours before starting the electrochemical test, which was conducted on an American Arbin BT2000 battery tester.
[0060] After assembly and power-on, the test was carried out. The test process was as follows: (1) Standing for 0.5 h; (2) Constant current discharge: 0.05C to 0.005 V; (3) Constant current charge: 0.05C to 2.0 V; (4) Standing for 15 min; the cut-off capacity was read as C0; (5) The specific capacity of the material (mAh / g) = C0 (mAh) / mass of active material (g).
[0061] 7. 72h electrode rebound rate After the negative electrode sheet is made, the temperature is maintained at 25°C and the humidity is less than 70%, and the thickness of the electrode sheet is tested at 0h and 72h.
[0062] 8. Pole resistance Measured by four-probe method.
[0063] 9. Disassembly status with full power Soft pack battery assembly: The negative electrode sheet in the above-mentioned embodiment and comparative example is used for preparation, and the battery also includes a positive electrode sheet, a diaphragm, an electrolyte and an aluminum-plastic film shell. Among them, the positive electrode sheet includes an aluminum foil with a thickness of 15μm, double-sided coating, and the density and thickness of the positive electrode active material layer on both sides of the aluminum foil are consistent. The total thickness of the positive electrode active material layer is 177.2μm, and the positive electrode active material layer includes NCM811, CNT, SP and PVDF in a mass ratio of 96.5:0.5:1.5:1.5. The electrolyte is a LiPF6 solution with a concentration of 1mol / L, and the solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1. The diaphragm is a polyethylene diaphragm with a thickness of 12μm. The battery made of the negative electrode sheet in the above-mentioned embodiment and comparative example is subjected to performance testing.
[0064] Full charge test process: 1) Stand at 25℃ for 3 minutes; 2) Charge at 1C constant current and constant voltage to 3.65V; 3) Stand for 3 minutes. After full charge, disassemble the battery to check the lithium deposition status.
[0065] 10. Soft pack battery cycle performance test process 1) Stand at 25℃ for 30min; 2) Charge at 1C constant current to 3.65V; 3) Stand for 30min; 4) Discharge at 1C constant current to 2.5V; 5) Stand for 30min; 6) Cycle 2) to 5) 1000 times. The discharge capacity of the 3rd and 1000th cycles are recorded as C3 and C 1000 , then 1000 cycles capacity retention rate = (C 1000 / C3)×100%.
[0066] 11. Soft pack battery DCR test process 1) At 25℃, stand for 30min; 2) 0.33C constant current discharge to 2.5V; 3) Stand for 30min; 4) 0.33C constant current constant voltage charge to 3.65V, cut-off current 0.05C; 5) Stand for 30min; 6) 0.33C constant current discharge to 2.5V, record the discharge capacity as C0; 7) Stand for 30min; 8) 1C0 constant current constant voltage charge to 3.65V, cut-off current 0.05C0; 9) Stand for 30min; 10) 0.33C0 constant current discharge to 50%C0 (adjusted to 50%SOC); 11) Stand for 60min, record the static terminal voltage V1; 12) 3C0 constant current discharge for 30s, record the voltage after discharge V2; 13) Stand for 40s; 14) 2.2C0 constant current charge for 15s; 15) Stand for 60min.
[0067] DCR= (V1-V2) / discharge current.
[0068] See the table below for specific test results.
[0069] Table 1 Test results of graphite negative electrode materials
[0070] Table 2 Electrical performance test results
[0071] It can be seen from the data in the above table that acid oxidation and N / P co-doping effectively improve the overall performance of the material. The acid oxidation treatment converts the two-dimensional graphite layer into an extended graphite layer with porous voids, expanding the interlayer space; N / P element co-doping exposes more lithium active sites to the material, promotes the transmission of lithium ions in the graphite layer, and thus greatly enhances the rapid charging ability of lithium ions. From the comparison of Comparative Examples 1 and 5 with the embodiments, it can be seen that the structure of the graphite negative electrode material obtained by single / high-content nitrogen doping is unstable. Although nitrogen doping improves conductivity and active sites, it may introduce too many structural defects, causing the material to easily delaminate or fragment during the cycle, affecting the cycle stability. In addition, single nitrogen doping may lead to uneven formation of SEI film, increase the formation of lithium precipitation phenomenon, and shorten battery life.
[0072] From the comparison between Comparative Examples 2 and 4 and their embodiments, it can be seen that single / high-content phosphorus doping has limited improvement on the conductivity of graphite negative electrode materials. Although phosphorus doping can improve structural stability, its effect on improving conductivity is not as obvious as nitrogen, and may not be able to fully meet the needs of high-rate discharge. Although phosphorus doping increases certain active sites, the capacity increase may not be as significant as that brought about by nitrogen doping.
[0073] From the comparison between Comparative Example 3 and the embodiment, it can be seen that it is difficult to achieve effective doping of elements by acid-free oxidation treatment using only a single element co-doping method, and the improvement of material capacity is very limited. The interlayer space is not significantly expanded and sufficient space cannot be provided for lithium ion insertion / migration, so the demand for high-rate discharge cannot be fully met.
[0074] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A graphite negative electrode material, characterized in that: The invention comprises acid-oxidized graphite, wherein the acid-oxidized graphite is doped with nitrogen and phosphorus. Based on the total mass of the graphite negative electrode material, the doping amount of the nitrogen is 0.5-3%, and the doping amount of the phosphorus is 0.5-4%.
2. The graphite negative electrode material according to claim 1, characterized in that: The specific surface area of the graphite negative electrode material is 1-3m 2 g -1 ; And / or, under a pressure of 10 MPa, the powder resistivity of the graphite negative electrode material is 0.5-2Ω·m.
3. The graphite negative electrode material according to claim 1 or 2, characterized in that: The OI value of the graphite negative electrode material is 1-10; And / or, the degree of graphitization of the acid-oxidized graphite is 90-98%.
4. A method for preparing the graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1, using an acid solution containing nitric acid to perform acid oxidation treatment on graphite to obtain acid oxidized graphite; S2, mixing the acid-oxidized graphite with a nitrogen source and a phosphorus source, and pyrolyzing them at 600-1200° C. for 0.5-2 h to obtain the graphite negative electrode material.
5. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: In step S2, the mass ratio of the acid-oxidized graphite, the nitrogen source, and the phosphorus source is 1:5-30:5-20.
6. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: In step S2, the nitrogen source includes at least one of urea, biuret, melamine, amino acid or ammonium carbonate; And / or, the phosphorus source includes at least one of sodium tripolyphosphate, red phosphorus, phosphoric acid, triphenylphosphine, and phosphorus pentachloride.
7. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: In step S1, the nitric acid-containing acid solution comprises concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:4-4:1; The concentration of the concentrated nitric acid is 55%-70%; the concentration of the concentrated sulfuric acid is 95%-98%.
8. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: In step S1, the acid oxidation treatment time is 12-36h; And / or, the temperature of the acid oxidation treatment is 15-20°C; And / or, the usage ratio of the graphite to the acid solution containing nitric acid is 1 g: 1-20 mL.
9. A secondary battery, characterized in that: The invention comprises the graphite negative electrode material according to any one of claims 1 to 3 or the graphite negative electrode material prepared by the preparation method according to any one of claims 4 to 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Nitrogen-doped graphite carbon serving as anode material of lithium ion battery, and preparation method and application thereof
CN102034975A
Preparation method of nitrogen, phosphorus and oxygen co-doped porous graphitized carbon nanosheet
CN112479199A
Preparation method of nitrogen-doped hard carbon coated artificial graphite composite material
CN113889596A
Nitrogen-doped expanded-layer graphite / tin phosphide multilayer composite material and preparation method thereof
CN114420936A
Graphite negative electrode composite material, preparation method thereof and lithium ion battery
CN115207304A
